TINJAUAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN NO. 16 TENTANG AKTIVA TETAP PADA PT. SUKSES TANI NUSA SUBUR PENAJAM PASER UTARA - -, Nurul Zanah (EKONOMIA, 2014)
This study aims to determine the extent to which the company applies the theory of SFAS No. 16, on the valuation of fixed assets in the financial statements PT.Sukses Tani Nusasubur.The problem of this study is, "Does the application of fixed assets in the financial statements of PT.Sukses Tani Nusasubur accordance with the statement of Financial Accounting Standards No. 16?. "Basic theory of financial accounting, and IAS 16.Based on the hypothesis of this study is the description of the background and the existing theoretical framework, the authors propose the following hypothesis: It was alleged that the presentation of fixed assets in the financial statements PT.Sukses Tani Nusasubur not in accordance with SFAS No. 16 and has led to profit and loss.The analytical tool used is intended to hold a comparative assessment of fixed assets in the financial statements conducted by PT. Sukses Tani Nusasubur whether pursuant to Accounting Standard 16 financial statement numbers.Based on the analysis and discussion that has been done before, it can be concluded that the hypothesis is accepted because it turns out assessment of Fixed Assets in the financial statements. PT.Sukses Tani Nusasubur not in accordance with SFAS 16 and has led to income by the following reasons:Fixed assets held and used for operations by PT. Sukses Tani Nusasubur obtained by cash and credit treatment is not fully in accordance with Statement of Financial Accounting Standards No. 16.Given these differences proved correct charging equipment as the cost of the project so that the company does not perform adequate supervision and control of the assets it has.With the presentation of the financial statements.PT.Sukses Tani Nusasubur with calculations according PSAKNo.16, there is a difference in earnings with the calculation according PSAKNo.16 with calculations according to the company, which the company said profit for the year amounted to Rp.600,000,000.00 and profit for the year under SFAS 16 is Rp. 942,574,350.00 means that there are differences in earnings of Rp.342,574,350.00. While the cost of depreciation company of Rp 193,706,000.00 and depreciation expense under SFAS 16 for Rp.307,897,450.00 means there are differences in the cost of Rp.114,191,450.00 so the need for adjusting entries necessary as a corrective adjustment in the valuation fixed assets 2012